ANALISIS KINERJA PEGAWAI DI KELURAHAN RABANGODU SELATAN KECAMATAN RABA KOTA BIMA - Arman Arman (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2022)
In order to build an effective and efficient quality of government performance, time is needed to think about how to achieve unity of cooperation so as to increase public trust. For this reason, autonomy and freedom are needed in making decisions on allocating resources, making service guidelines, budgets, goals, and clear and measurable performance targets. Kelurahan as a government organization that is closest and directly related to the community is the spearhead of the success of urban development, especially regional autonomy, where the kelurahan will be directly involved in planning and restoring development and services. It is said to be the spearhead because the kelurahan deals directly with the community, therefore the kelurahan must be able to become a place for the community to be resolved. In the current reform era, the government's performance has received sharp attention from the public. With the freedom to express opinions (aspirations), there are many scathing criticisms of the government's performance, either directly (through official forums or even demonstrations) or indirectly (through writings or letters from readers in the mass media). The criticism is without exception from the central government to the lowest government, namely the village government